Dynamic Supination in Congenital Clubfoot: A Modified Delphi Panel Approach to Standardizing Definitions and Indications for Treatment. Issue 5 (18th May 2022) - Baskar, Danika; Hosseinzadeh, Pooya; Mosca, Vincent; Bouchard, Maryse; Aroojis, Alaric; Arkader, Alexandre; Cidambi, Emily; Denning, Jaime; Eastwood, Deborah; Gantsoudes, George; Kelly, Derek M.; Kishta, Waleed; et al.
Abstract : Background: Dynamic supination is a well-recognized cause of congenital clubfoot deformity relapse. However, there is no consensus on how to diagnose it and there are varied approaches in its management. This study aims to define dynamic supination and indications for treatment by presenting consensus from an international panel of experts using a modified Delphi panel approach. Methods: An international panel of 15 pediatric orthopaedic surgeons with clinical and research expertise in childhood foot disorders participated in a modified Delphi panel on dynamic supination in congenital clubfoot. Panelists voted on 51 statements using a 4-point Likert scale on dynamic supination, clinical indications for treatment, operative techniques, and postoperative casting and bracing. All panelists participated in 2 voting rounds with an interim meeting for discussion. Responses were classified as unanimous consensus (100%), consensus (80% or above), near-consensus (70% to 79%), and indeterminate (69% or less). Results: Consensus was achieved for 34 of 51 statements. Panelists agreed dynamic supination is present when the forefoot is supinated during swing phase of gait with initial contact on the lateral border of the foot. There was also agreement that dynamic supination results from muscle imbalance between the tibialis anterior and the peroneus longus and brevis. There was no consensus on observation of hindfoot varus in dynamic supination, operative indications for posterior release of the ankle joint, or incisional approach for tibialis anterior tendon transfer. Reference to the calcaneopedal unit concept, planes of movement, and phases of gait were deemed important factors for consideration when evaluating dynamic supination. Conclusions: Consensus statements from the Delphi panel can guide diagnosis and treatment of dynamic supination in clubfoot deformity relapse, including clinical decision making regarding preoperative casting, surgical approach, and postoperative immobilization. Near-consensus and indeterminate statements may be used to direct future areas of investigation. Level of Evidence: Level V.